Effects of riparian buffer and stream channel widths on ecological indicators in the upper and lower Indus River basins in Pakistan - Hira, Amin; Arif, Muhammad; Zarif, Nowsherwan; Gul, Zarmina; Xiangyue, Liu; Yukun, Cao (Frontiers in Environmental Science, 2023)
Riparian buffers and stream channel widths along river networks have extremely significant ecological influences on parameters and stressors associated with riparian health indicators (RHIs). It is imperative for countries that rely heavily on rivers for irrigation to protect RHIs such as habitat, plant cover, regeneration, exotics, and erosion. It is unclear which protection methods are most effective for RHIs in less developed countries, such as Pakistan. This study fills this gap by using a quick field-based technique that includes 273 transects and examines the response of RHIs in the upper and lower Indus River basins (IRB). In the lower Indus basin (LIB), riparian buffer and stream channel widths had the most considerable influence on RHIs using Pearson’s correlations, ranging from ̶ 0.47 < r < 0.71 and ̶ 0.41 < r < 0.32, respectively. There was a significant relationship between stressors and RHIs in the LIB when these widths were changed, and stressors had a significant influence on habitat ̶ 0.37 < r < 0.41, plant cover ̶ 0.32 < r < 0.38, regeneration ̶ 0.29 < r < 0.25, erosion ̶ 0.34 < r < 0.49, and exotics ̶ 0.39 < r < 0.24. In contrast, these stressors in the upper Indus basin (UIB) also adversely affected habitat ̶ 0.28< r < 0.27, plant cover ̶ 0.34 < r < 0.26, regeneration ̶ 0.19 < r < 0.26, erosion ̶ 0.38 < r < 0.23, and exotics ̶ 0.31 < r < 0.30. It was found from the principal component analysis that the responses of RHIs and stressors varied considerably between the UIB and LIB. Additionally, the agglomerative hierarchical cluster analysis of the RHIs and stressor indices revealed dissimilarities in the UIB and LIB. This study supports the need to examine riparian regions along long rivers, which are subject to the same administrative strategies. Large river ecosystems need revised standards to prevent further degradation based on ecological indicators.